2017
DOI: 10.1177/1555343416686476
|View full text |Cite
|
Sign up to set email alerts
|

Intuitive Cognition

Abstract: In the naturalistic decision-making literature, intuitive cognition is at the heart of a pattern recognitionbased decision model called the recognition-primed decision model. Given the importance of intuitive cognition in naturalistic decision-making theory, we explore the question of what makes intuitive cognition effective for decision making and, in so doing, present an extended empirical and theoretical foundation for the intuitive component in naturalistic decision making. We theorize that intuitive cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 139 publications
(230 reference statements)
0
12
0
1
Order By: Relevance
“…Neuroscientific research has shown that neural activity predicting voluntary movement can be discerned as much as ten seconds before a person becomes aware of an urge to move, and, further, that the prefrontal cortex can affect behavior in response to clues that do not appear in consciousness (Isenman, 2018, p. xiii). Intuitive cognition is thus critical in decision making (Patterson & Eggleston, 2017).…”
Section: Defining Intuiting and Intuitionmentioning
confidence: 99%
“…Neuroscientific research has shown that neural activity predicting voluntary movement can be discerned as much as ten seconds before a person becomes aware of an urge to move, and, further, that the prefrontal cortex can affect behavior in response to clues that do not appear in consciousness (Isenman, 2018, p. xiii). Intuitive cognition is thus critical in decision making (Patterson & Eggleston, 2017).…”
Section: Defining Intuiting and Intuitionmentioning
confidence: 99%
“…Analytical cognition is deliberate and conscious, requiring executive control functions to inhibit automatic responses, utilize working memory, and actively select and modulate schema (Baddeley, 2003). On the other hand, intuitive cognition involves automatic selection of schema based on pattern recognition that is independent from executive control and unconstrained by working memory (Patterson & Eggleston, 2017). The structured, systematic decision-making processes of an analytic cognitive style require increased planning, attention, and delay of rewards; all of which would be expected to create information- and task-related challenges for individuals with ADHD (Lerner et al, 2018b; Wiklund et al, 2018).…”
Section: Theoretical Overviewmentioning
confidence: 99%
“…Our computational model of the vigilance decrement can be placed within the context of dual-process theory (Patterson, 2017;Patterson & Eggleston, 2017). According to this theory, human reasoning and decision making are mediated by two distinct sets of cognitive processes or systems: analytical and intuitive cognition.…”
Section: Discussionmentioning
confidence: 99%